Mentalization-Based Treatment in Groups for Adults With Autism Spectrum Disorder - Krämer, Katharina; Vetter, Annekatrin; Schultz-Venrath, Ulrich; Vogeley, Kai; Reul, Sophia (Frontiers in Psychology, 2021)
In order to successfully interact with others in social encounters, we have to be attentive to their mental states. This means, we have to implicitly and explicitly interpret our own actions as well as the actions of others as meaningful on the basis of the ascription of intentional mental states. However, this ability, often referred to as mentalizing, seems to be impaired in autism spectrum disorder (ASD). Individuals with ADS show specific deficits relating to the representation of mental states of others. Especially, the spontaneous, intuitive attribution of and reaction to others’ mental states seem to be impaired. Mentalization-Based Treatment (MBT) is a form of psychotherapy in individual and group settings that focuses on the education and enhancement of mentalizing. Although the scope of MBT is broad and MBT has been already proven to be useful in a variety of mental disorders, no attempt has been made to apply MBT in patients with ASD. In our study, we adapted MBT for adults with ASD in a therapeutic group setting to examine the feasibility as well as the effectiveness of the treatment in this patient group. During 15 to 20 weeks of weekly group therapy, we surveyed the patients’ acceptability of the intervention. Additionally, changes in mentalizing difficulties were measured before and after treatment. Results show a high acceptance of the treatment and an improvement in the patients’ mentalizing abilities, presenting MBT as a promising treatment option for ASD.